Science:Core regulator of rice immunity: The role of classical protein complexes on homeostasis and multipathogen resistance - Shutian Liu; Zenglong Chen (Advanced Agrochem)
Plants have evolved complex immune networks to adapt to survival needs, and their immune mechanisms have unique regulatory patterns to cope with different environments. In rice, the maintenance of immune balance involves the synergistic action of many factors. Yue Wu et al. 's latest research results on the immunomodulatory mechanism of rice (ROD1 and the interaction between various proteins in rice) are introduced in this paper.